2015
DOI: 10.5296/ajfa.v7i2.8404
|View full text |Cite
|
Sign up to set email alerts
|

The Vital Role of Gender Diversity on Corporate Outcomes: The Need for Empirical Studies Concerning Frontier Markets

Abstract: The purpose of the study is to review empirical studies related to gender diversity on corporate outcomes and suggest the need for more empirical research on gender diversity in frontier markets. Several empirical studies have identified the need for a critical mass of female directors and executives in corporate firms. This review further justifies the clamour for more female representation on boards globally. Nigeria is a country that has very weak corporate governance compared to the United States (US) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the impact of gender diversity in corporate boardrooms remains contentious. Extant literature has documented that the association between gender diversity and market measures is mixed (Abdullah and Ku Ismail, 2013;Badru et al, 2015). Some have found it to be detrimental (Adams and Ferreira, 2009), whilst others have found it to be insignificant (Carter et al, 2010;Rose, 2007).…”
Section: Robustness Testsmentioning
confidence: 99%
“…Therefore, the impact of gender diversity in corporate boardrooms remains contentious. Extant literature has documented that the association between gender diversity and market measures is mixed (Abdullah and Ku Ismail, 2013;Badru et al, 2015). Some have found it to be detrimental (Adams and Ferreira, 2009), whilst others have found it to be insignificant (Carter et al, 2010;Rose, 2007).…”
Section: Robustness Testsmentioning
confidence: 99%
“…Evidence suggests that strategic change, strategic leadership, external environment and their relationship to TMT diversity and performance may be a fruitful area for further exploration. The review found some previous research showing mixed or negative effects of TMT diversity (Cannella & Monroe, 1997;Elsaid 2012;Bagudu & Abdulmumini 2015) and by the suggestion that TMT diversity not only has positive cognitive implications but also negative social implications (Hambrick et al, 1996;Haleblian & Finkelstein 2013). As Jarzabkowski & Rosalind (2003) recently argued, these teams may suffer from behavioural disintegration i.e., less communication within teams and a lower likelihood of reaching consensus with new ideas and strategic initiatives being the first to suffer (Priem, Lyon & Dess, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Some empirical studies conducted recently in some developed and emerging economies reported a significant association between ethnic diversity and the extent of voluntary disclosure [51][52][53]. Conversely, other empirical shreds of evidence presented (e.g., [5,54]) have all shown a negative influence on firms' voluntary disclosure. For instance, Bravo [55] empirically investigated whether ethnic diversities have any influence on corporate disclosure and suggested that the disclosure of crucial information in the capital markets is significantly improved by ethnic diversity.…”
Section: Effect Of Ethnic Diversity On Voluntary Disclosurementioning
confidence: 98%